1. To find the series of odd numbers we use the general odd number formula (2n+1).
2. The 'nth' term of this arithmetic sequence, represented as 'an', can be computed using the formula: an = a + (n – 1) d. The total sum of the arithmetic series, denoted as 'Sn', can be calculated through the formula: Sn = n/2 (2a + (n – 1) d) (or) Sn = n/2 (a + an).
3. Sequence and Series Formulas
|
Arithmetic Progression |
Geometric Progression |
General Term (nth Term) |
an = a + (n-1)d |
an = ar(n-1) |
nth term from the last term |
an = l – (n-1)d |
an = l/r(n-1) |
Sum of first n terms |
sn = n/2(2a + (n-1)d) |
sn = a(1 – rn)/(1 – r) if |r| < 1 sn = a(rn -1)/(r – 1) if |r| > 1 |